Genome Sequence of Klebsiella pneumoniae Strain LCT-KP182, Which Acquired Hemolytic Properties after Space Flight - Zhang, Xiaojun (American Society for Microbiology, 2014)
The Klebsiella pneumoniae strain LCT-KP182 acquired hemolytic properties after space flight. Here, we present the draft genome sequence of this strain.